Recombinase-mediated gene stacking in cotton. Issue 4 (28th January 2022) - Li, Yamei; Li, Ruyu; Han, Zhiguo; Wang, Haitang; Zhou, Sixian; Li, Yongqing; Wang, Yumei; Qi, Junsheng; Ow, David W
Abstract : Cotton target lines suitable for in planta gene stacking can be used to stack verticillium wilt resistance genes. Abstract: Site-specific gene stacking could reduce the number of segregating loci and expedite the introgression of transgenes from experimental lines to field lines. Recombinase-mediated site-specific gene stacking provides a flexible and efficient solution, but this approach requires a recombinase recognition site in the genome. Here, we describe several cotton ( Gossypium hirsutum cv. Coker 312) target lines suitable for Mycobacteriophage Bxb1 recombinase-mediated gene stacking. Obtained through the empirical screening of random insertion events, each of these target lines contains a single intact copy of the target construct with precise sequences of RS2, lox, and attP sites that is not inserted within or close to a known gene or near a centromere and shows good expression of the reporter gene gfp . Gene stacking was tested with insertion of different combinations of three candidate genes for resistance to verticillium wilt into three cotton target lines: CTS1, CTS3, and CTS4. Nine site-specific integration events were recovered from 95 independently transformed embryogenic calluses. Southern and DNA sequence analyses of regenerated plants confirmed precise site-specific integration, and resistance to verticillium wilt was observed for plant CTS1i3, which has a single precise copy of site-specifically integrated DNA. These cotton target lines can serve as foundation lines for recombinase-mediated gene stacking to facilitate precise DNA integration and introgression to field cultivars.